MineLab 360: safe science, infinite discovery - Md Shamsudin, Nurshamshida; Ibrahim, Norezan; Firus Khan, Al’ Aina Yuhainis (2025)
MineLab 360: Safe Science, Infinite Discovery is an educational innovation that leverages the immersive potential of Minecraft Education Edition to transform the way science is taught in schools. Designed as a multidisciplinary virtual lab, MineLab 360 enables students to explore hazardous experiments in Biology, Chemistry, and Physics within a safe, engaging, and gamified environment. The innovation addresses key challenges in science education, including limited access to functional laboratories, safety restrictions on physical experiments, and low student engagement with abstract scientific concepts. By simulating real-life experiments—such as virtual dissections, compound synthesis, pH testing, circuit construction, and motion analysis, students develop scientific inquiry skills without the risks associated with traditional lab settings. Unique features of MineLab 360 include curriculum-aligned virtual worlds, built-in lab safety training, interactive NPC guides, and in-game journals for student documentation and reflection. This approach supports both in-person and remote learning, making it accessible to schools with limited infrastructure or during disruptions such as pandemics. The innovation promotes equitable STEM education, enhances digital fluency, and supports the integration of 21st-century skills into science instruction. MineLab 360 has been implemented in science teacher education programs has received positive feedback from both educators and learners. MineLab360 is in the process of intellectual property registration under MyIPO as a digital instructional module and immersive science teaching kit. MineLab 360 represents a sustainable, scalable solution for safe, inquiry-driven, and future-ready science education.